INNOVATIVE TECHNOLOGIES IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (British Journal of Global Ecology and Sustainable Development, 2023)
Over the past decade, the use of innovative technologies in the method of teaching the Russian language as a foreign language has become more and more relevant. This article provides an overview of materials on modern computer technologies released over the past few years. The methods of research were descriptive, continuous sampling, statistical analysis. During the study, the main directions were identified that allow us to draw conclusions about the possibilities of using and expediency of using innovative technologies in the process of teaching the Russian language to foreigners. The significantly increased number of publications on the declared topic indicates the prospects for innovative technologies in classes in a foreign audience.